4-Methylcatechol-treated Jute-Bamboo Hybrid Composites: Effects of pH on Thermo-Mechanical and Morphological Properties - Fui, Kiew Liew; Sinin, Hamdan; Md Rezaur, Rahman; Mohamad Rusop, Mahmood; Md. Mizanur, Rahman; Chang, Josephine Hui Lai; Md. Tipu, Sultan (BioResources, 2016)
Hybrid composites were fabricated with 4-methylcatechol-treated jute and bamboo fiber at different pH levels. The effects of different pH levels on the thermal, mechanical, and morphological properties of jute-bamboo hybrid composites were investigated. Fabricated hybrid composites were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), dynamic mechanical thermal analysis (DMTA), and adhesion test analysis. Additionally, surface morphology and tensile testing were reported. Fourier transform infrared spectroscopy (FTIR) revealed that the peak intensities at 1634 and 1643 cm-1 disappeared in treated jute and bamboo fibers. This resulted from the removal of hydroxyl groups on the treated fibers. A higher pH (9 or 10) resulted in the effective modification of bamboo and jute fibers. The TGA results showed that the presence of hybrid fiber led to an earlier degradation of the hybrid composite. The DSC results showed that the crystallinity index declined by 7% to 8%, which improved the adhesion between the fiber and the polymer. According to these finding, the pH level contributed to an improvement in the mechanical properties of the composites. The pH 10-treated hybrid composites exhibited the highest tensile strength and modulus. The surface morphology revealed that at higher pH, the treated hybrid composites exhibited strong adhesion characteristics.